2014
DOI: 10.1038/ncb3025
|View full text |Cite
|
Sign up to set email alerts
|

Mammary stem cells have myoepithelial cell properties

Abstract: Contractile myoepithelial cells dominate the basal layer of the mammary epithelium and are considered to be differentiated cells. However, we observe that up to 54% of single basal cells can form colonies when seeded into adherent culture in the presence of agents that disrupt acin-myosin interactions, and on average, 65% of the single-cell-derived basal colonies can repopulate a mammary gland when transplanted in vivo. This indicates that a high proportion of basal myoepithelial cells can give rise to a mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 34 publications
11
203
1
Order By: Relevance
“…Contrary to predictions from the literature and the progenitor potential of myoepithelial cells in other organs, we found no evidence for the capacity of the myoepithelial lineage to contribute to other epithelial lineages in adult lacrimal glands (Makarenkova and Dartt, 2015;Prater et al, 2014;Zoukhri et al, 2007Zoukhri et al, , 2008. Rather, the maintenance of labeled cells after extensive chasing suggested that myoepithelial cells replenish themselves.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Contrary to predictions from the literature and the progenitor potential of myoepithelial cells in other organs, we found no evidence for the capacity of the myoepithelial lineage to contribute to other epithelial lineages in adult lacrimal glands (Makarenkova and Dartt, 2015;Prater et al, 2014;Zoukhri et al, 2007Zoukhri et al, , 2008. Rather, the maintenance of labeled cells after extensive chasing suggested that myoepithelial cells replenish themselves.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have implicated myoepithelial cells as epithelial progenitors, but genetic lineage tracing of these cells has not been reported (Makarenkova and Dartt, 2015;Prater et al, 2014;Zoukhri et al, 2008). We genetically labeled myoepithelial cells in adult RFP reporter mice using the Acta2…”
Section: Novel Insights Into Myoepithelial Cell Differentiation and Omentioning
confidence: 99%
“…Lineage-tracing studies in mice have confirmed the existence of bi-potent basal MaSCs in the mammary gland in situ (Rios et al, 2014;van Amerongen et al, 2012), as well as identified lineagerestricted unipotent luminal and basal stem/progenitor cells (van Amerongen et al, 2012;Van Keymeulen et al, 2011), which likely together drive postnatal mammary gland morphogenesis in a dynamic fashion (Rios et al, 2014;van Amerongen et al, 2012). Moreover, in vitro and in vivo functional studies suggest that differentiated luminal and myoepithelial cells possess a remarkable plasticity and can dedifferentiate into basal MaSCs (Chaffer et al, 2011;Prater et al, 2014). However, the molecular mechanisms governing MaSC regulation in vivo remain ill defined.…”
Section: /Sca1mentioning
confidence: 90%
“…For example, the use of matrigel to prevent anoikis, and the injection of epithelia in their native configuration with attached stroma, both strongly increased gland reconstitution efficiency (Spike et al, 2012). Likewise, the culture of myoepithelial cells for one week in vitro was sufficient to massively increase MRU activity (Prater et al, 2014). Given these many potential variables, a consensus technical paper, comparing leading separation methods and providing guidance for future studies, has been published (Smalley et al, 2012).…”
Section: Issues With Mru Studiesmentioning
confidence: 99%
“…2). Nonetheless, recent work suggests that the cells isolated via the sorting approach described above are all myoepithelial: myoepithelial cells expressing smooth muscle actin were the only cells able to repopulate the gland in one recent study (Prater et al, 2014). FACS and gland reconstitution from 8-12-week-old mice (in 50% matrigel)…”
Section: Markers and Features Of Mammary Gland-reconstituting Cellsmentioning
confidence: 99%